Session-Oriented Communication System for Truly Reliable and Robust Smart Grid - Neto, Augusto (2011)
Environmental sustainability issues and the costs of new power generation and transmission have increased the interest in evolving current power grid to new technologies. The Smart Grid is a promising technology, since it allows a distributed computing approach with potentials for selfdiagnosing/-healing, reliable multi-user communication and fast hard real-time control. However, the missing standardization associated with heterogeneity of legacy systems and wide-area service demands, makes very challenging to adopt Smart Grid in a cost-effective way. By considering this, we propose the Session-Oriented communication System (SOCSys) to overcome the above issues by enhancing Smart Grid with truly reliable and robust capabilities over heterogeneous environments. SOCSys achieves this goal by orchestrating session-control with innovative network-centric facilities operating over a wireless mesh Information Network compliant with IEEE 802.11e/s standard. The simulation results show that SOCSys improved network performance in terms of bandwidth utilization and minimization of delay, while consuming low network resources. Graphical analyses showed that SOCSys supported multimedia sessions with excellent quality, where it outperforms the experiments with regular settings. In this field, Smart Grid management demands capabilities to deal with [2]: distribution fault anticipation; problem detection on smart switches and reclosers; fast fault isolation and power rerouting; and adaptive energy storage systems to store and release energy at sub-cycle control loop rates. Such applications require Intelligent Electronic Devices (IED) publishing, in suitable time, metering data (status and consume). For that, the Advanced Metering Infrastructure (AMI) was conceived to supply diversity and high quality metering data in near real-time, so that improve detecting events in time to respond.